Nonlinear optical response of α -terpinolene and β -phellandrene chromophores: An octupolar gas-to-solvent enhancement able to retain light conduction - dos Santos, Neidy S. S. (2023)
The search for new materials with improved nonlinear optical (NLO) response is a field of growing interest in materials science. Typically, the dipole ΦJ=1 contributions exceed the octupolar ΦJ=3 ones and dominate the optical behavior. However, the latter is essential for NLO device engineering. Under this scenario, this work investigates the electronic-optical properties of the α-terpinolene and β-phellandrene molecules within the Hyper-Rayleigh scattering formalism (HRS). It includes solvent contributions using a sequential Monte Carlo/Quantum Mechanics procedure. According to Density Functional Theory analysis, molecular solvatochromism acts differently for the two chromophores. While α-terpinolene undergoes a hypsochromic effect, the β-phellandrene molecule shows moderate bathochromism, both with a strong absorption band in the ultraviolet region (λmax<240nm), making them attractive for potential UV filters. Regarding the NLO response, both compounds present similar values for the first frequency-dependent hyperpolarizability (βHRS) with values that vary from 62.46 to 138.73 au in aqueous environment, superating urea (β=42.82 au), a standard optical material. Furthermore, while one of these chromophores is best described by dipole contributions (ΦJ=1≈68%), the other is dominated by the octupolar term (ΦJ=3≈60%) even when the solvent moderates it. These characteristics allow the building of optical switches without losing the strength of the NLO response. In addition, the polarization of the solute due to the solvent conveniently reduces the refractive index (n), providing light conduction applications. Therefore, these chromophores can be used to promote a decoupling between dipolar and octupolar contributions in NLO.